Differential Evolution Algorithm for Multistage Transmission Expansion Planning Based on AC Load Flow Model - Alhamrouni, I; Bin Khairuddin, A; Ferdavani, A.K; Salem, M; Alnajjar, A (3rd IET International Conference on Clean Energy and Technology (CEAT) 2014, 2014)
This work proposes a method based on a mixed integer nonlinear non-convex programming model to solve the multistage transmission expansion planning (TEP). A metaheuristic algorithm by the means of differential evolution algorithm (DEA) is employed as an optimization tool. An AC load flow model is used in solving the multistage TEP problem, The proposed technique is tested on the Colombian 93 bus system and has shown high capability in considering the active and reactive power in the same manner and solving the TEP problem. The method produced improved good results in a faster convergence time for the test systems.